2021
DOI: 10.1073/pnas.2025273118
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of an otherwise rare phenotype in a small and isolated tiger population

Abstract: Most endangered species exist today in small populations, many of which are isolated. Evolution in such populations is largely governed by genetic drift. Empirical evidence for drift affecting striking phenotypes based on substantial genetic data are rare. Approximately 37% of tigers (Panthera tigris) in the Similipal Tiger Reserve (in eastern India) are pseudomelanistic, characterized by wide, merged stripes. Camera trap data across the tiger range revealed the presence of pseudomelanistic tigers only in Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 106 publications
(156 reference statements)
0
23
0
Order By: Relevance
“…1 A and B ). We compared our estimates for zoo individuals with their known pedigree values to authenticate these results and found that estimates of recent inbreeding indeed correspond with pedigree values ( 51 ) ( SI Appendix , Table 1 ). Overall, the long ROH of 10 Mb, signifying inbreeding due to ancestors as recent as three generations ago, are rare in large populations but frequent in the small–isolated population.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…1 A and B ). We compared our estimates for zoo individuals with their known pedigree values to authenticate these results and found that estimates of recent inbreeding indeed correspond with pedigree values ( 51 ) ( SI Appendix , Table 1 ). Overall, the long ROH of 10 Mb, signifying inbreeding due to ancestors as recent as three generations ago, are rare in large populations but frequent in the small–isolated population.…”
Section: Resultsmentioning
confidence: 69%
“…We collected tissue from tranquilized or dead tigers from several tiger reserves (14 protected areas across India); zoo individuals from Sagar et al. ( 51 ) were also analyzed ( Fig. 5 and SI Appendix , Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, individuals in the fragmented forest could also be darker due to inbreeding and/or low genetic diversity. Rare (often melanic) pigmentation phenotypes can arise in other taxa due to increased inbreeding (Larison et al, 2021) or population bottlenecks (Sagar et al, 2021). Although previous work indicates identical mitochondrial haplotypes in groups sampled across Tsinjoarivo, mitochondrial DNA may not always accurately estimate relatedness between individuals or populations (Guschanski et al, 2013; Mayor et al, 2004; Meyer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%